Comparison of phytoplankton community structure in two tropical estuaries of East Coast of India - Chowdhury, Chumki (Current Botany, 2020)
Phytoplankton community of two tropical river estuaries of the North-east coast of India was different due to dissolved nutrients concentration in those estuarine waters. The first study site was the Saptamukhi river estuary which is located in the Indian Sundarban (inside mangrove forest) and the second study site was Mahanadi estuary located in Orissa coast (adjacent to industrial and coastal fishing zone). The Saptamukhi estuary was mostly devoid of any anthropogenic influence and here the nutrient source was auto-generated. In Mahanadi estuarine water, the source of the major nutrients was industrial effluent and fishing waste. The Saptamukhi estuarine water had less dissolved phosphorus concentration but huge dissolved nitrogen available for phytoplankton uptake. A sufficient amount of dissolved silicate encouraged the diatom growth over other phytoplankton groups here. Due to the availability of the high amount of dissolved phosphorus and the low amount of dissolved nitrogen in the Mahanadi estuary the phytoplankton community was a mixed population of Bacillariophyceae, Cyanophyceae, Chlorophyceae and Dinophyceae and seasonal Chlorophycean bloom observed during the study period. In both the estuarine water primary productivity was high but the community respiration was higher and the estuaries were heterotrophic. Monsoonal runoff from land considerably changed the community in both estuarine water. Dissolved silicate concentration in both the estuarine water was sufficient for Diatom growth. Dissolve inorganic nitrogen and dissolved inorganic phosphate ratio played a major role for the community change of phytoplankton in two estuarine waters.